ANALISIS PERAN KEBIJAKAN MONETER BANK INDONESIA (BI) RATE TERHADAP NILAI TUKAR US DAN INFLASI - Saridawati Saridawati (Universitas Bina Sarana Informatika, 2015)
Many things certainly affecting the depreciation of the rupiah against the US dollar. Certainly one of them is the amount of demand and supply on the US dollar itself. On one hand, the fulfillment of the various needs of society in the country form the background so that the import policy was taken. On the other hand, payments using the US dollar against the needs of the imported product, of course, will raise the demand for the US dollar. Meanwhile, the rupiah against the US dollar is one of the important factors that affect the domestic price changes. Price changes in this country, if not controlled properly will lead to inflation. This can be seen from the trend of depreciation of the rupiah against the US dollar followed by a rise in the inflation rate in the country. BI Rate is one of the policy instruments that are owned by the government to reduce the amount of money in circulation, so as to control the rate of growth of inflation. Keywords : BI Rate, Rupiah, US Dollar, Inflation